Regulation of the Maturity of Married Age in Suku Anak Dalam Jambi Province - Hidayati, Rahmi; Yuliatin, Yuliatin; Syuib, Kholil (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
There have been many previous studies that discussed the theme of early marriage, but the difference from this study is that the people studied are in the majority of isolated communities in Jambi Province (Suku Anak Dalam). The Suku Anak Dalam community has its own rules regarding the practice of marriage and overrides the provisions in the law that have been positive. One of these rules is related to how to measure the maturity of the bride and groom (marriage age limit). For them, girls who have reached puberty are considered capable of getting married, while boys who are mature are marked by a test of dexterity to hunt animals. If the boy passes / passes the test, then he is considered an adult and is able to get married. Because according to the women of the Anak Tribe, the concept of a man's valor lies in his ability to earn a living and hunt. This coincides with the lack of fulfillment of the rules set by the State as stated in Law no. 1 of 1974. This study wants to see what factors cause early marriage and this perspective.